2009
DOI: 10.1111/j.1365-2672.2008.04065.x
|View full text |Cite
|
Sign up to set email alerts
|

Cell wall component and mycotoxin moieties involved in the binding of fumonisin B1and B2by lactic acid bacteria

Abstract: Aims:  The ability of lactic acid bacteria (LAB) to bind fumonisins B1 and B2 (FB1, FB2) in fermented foods and feeds and in the gastrointestinal tract could contribute to decrease their bioavailability and toxic effects on farm animals and humans. The aim of this work was to identify the bacterial cell wall component(s) and the functional group(s) of FB involved in the LAB–FB interaction. Methods and Results:  The effect of physicochemical, enzymatic and genetic treatments of bacteria and the removal/inactiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
80
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(88 citation statements)
references
References 37 publications
6
80
1
1
Order By: Relevance
“…It was demonstrated that binding is the main mechanism involved in fumonisin removal, with adhesion to LAB cell wall components occurring rather than covalent binding or metabolism (Dalié et al, 2010;Niderkorn et al, 2009;Zhao et al, 2016). Our preliminary results were in agreement with binding mechanism since fumonisin removal was observed in presence of both live and dead LAB (unpublished data).…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…It was demonstrated that binding is the main mechanism involved in fumonisin removal, with adhesion to LAB cell wall components occurring rather than covalent binding or metabolism (Dalié et al, 2010;Niderkorn et al, 2009;Zhao et al, 2016). Our preliminary results were in agreement with binding mechanism since fumonisin removal was observed in presence of both live and dead LAB (unpublished data).…”
Section: Discussionsupporting
confidence: 81%
“…and FB2, varies with bacterial species (Niderkorn et al, 2009;Zhao et al, 2016). with all the strains exhibiting higher binding for FB2 than FB1.Binding ratio increased with a decline in pH from 6 to 2 and an increase in incubation temperature from 30°C to 37°C.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…(Galvano et al,1998), (Nageswara and Chopra, 2001) (Avantaggiato et al,2007) (Bursian, 2004), (Diaz et al,2004), (Chowdhury and Smith, 2005), (Kogan and Kocher, 2007), (Dvorska, 2007), (Smith et al,2008), (Moschini et al,2008), fusaric acid (Meissonnier et al,2009) ( Niderkorn et al,2006), (Niderkorn et al,2007), (Niderkorn et al,2008), (Niderkorn et al,2009) 20g/l OTA REALDYME (Tangni 2003, (Tangni et al,2005, (Aoudia et al,2008), (Aoudia et al,2009) 13. Antitox Vana (Polyvinylpolypyrrodilone, C 6 H 9 NO) 20g/l DON Qualitech Products Inc. (Friend, 1984) 2.…”
mentioning
confidence: 99%